Identifikasi Taman Setra di Desa Selat, Kecamatan Susut, Kabupaten Bangli, Provinsi Bali - Yasa, I Made Rai Semara; Sugianthara, Anak Agung Gede; Pradnyawathi, Ni Luh Made (Jurnal Arsitektur Lansekap; Vol.8, No.1, April 2022, 2022)
Identification of taman setra (balinese graveyard) in Selat Village, Susut District, Bangli Regency, Bali Province .This research was taken due to the fact that Taman Setra (Balinese graveyard) belongs to one of the Balinese Traditional Parks. Even so, there is also the fact that the existence of Taman Setra provide concepts that make Taman Setra different from other parks in general terms. Mainly, this study aimed to identify the Taman Setra’s spatial patterns, elements, functions, and benefits, particularly those that were located in the Selat Village. The research method used was a survey method with data collection techniques through interviews, field observation, and literature study. Based on the research, it was found that the hard elements of Taman Setra were such as prajapati, wantilan, and pemuhunan. Those elements were found in all the Taman Setra in Selat Village. On the other hands, the soft elements were also found almost in all Taman Setra, but in some Setra, there were plants that were deliberately tampered for the purposes of the ceremony. Furthermore, each element of the Taman Setra had a different function. This would relate to the results of this study that the spatial pattern of the Setra was influenced by a combination of age, caste, and tradition as the basic concept. Lastly, the benefits of Taman Setra in general were: as a place for burial, a place to burn the corpse, and a place for ceremonies.